The effect of life events, resilience, self-esteem, and coping styles on aggressive behavior among left-behind adolescents: Structural equation modeling - Zhang, Jie; Li, Yifei; Li, Juan; Lyu, Mengmeng; Chen, Yiping; Yang, Silan; Tan, Chuxia; Tao, Yingxiang; Ye, Biyun; Zhang, Jingping; Cheng, Fangqun; Mao, Ting (Frontiers in Psychiatry, 2023)
Without parental support, left-behind adolescents are more likely than their peers to experience negative emotions and demonstrate aggressive behavior in the same frustrating situation. However, research on this subject has been sparse. To fill this gap and identify potential targets for intervention, this study sought to examine the relationships among factors influencing left-behind adolescents' aggressive behavior. A total of 751 left-behind adolescents were enrolled in a cross-sectional survey, with data collected using the Adolescent Self-Rating Life Events Checklist, Resilience Scale for Chinese Adolescents, Rosenberg Self-Esteem Scale, Coping Style Questionnaire, and Buss-Warren Aggression Questionnaire. The structural equation model was used for data analysis. The results showed that left-behind adolescents reported higher levels of aggression. Further, the factors found to have a direct or indirect effect on aggressive behavior included life events, resilience, self-esteem, positive coping, negative coping, and household income. The results of confirmatory factor analysis indicated goodness of fit. In the face of negative life events, left-behind adolescents with high resilience, self-esteem, and positive coping were less likely to exhibit aggressive behavior (P < 0.05). These results suggest that left-behind adolescents can reduce their aggressive behavior by assuaging the adverse effects of life events via increased resilience and self-esteem as well as the adoption of positive coping strategies.